TEXTILE AND APPAREL SUPPLY CHAIN: STRUCTURE, COMPLEXITY, AND TRENDS OF GLOBAL TRANSFORMATION (Editora Impacto Científico, 2025)
The textile and apparel supply chain occupies a strategic position in the global and Brazilian economy, being recognized for its productive relevance and value generation capacity. However, it faces challenges related to its high complexity, transformations in international trade, and increasing pressure for sustainable and digital practices. This article aims to structure and characterize the main links that make up the textile and apparel supply chain, identifying their interactions, specificities, and implications for strategic management. Methodologically, a systematic literature review was conducted, based on articles indexed in the Scopus and Web of Science databases, complemented by bibliometric analysis to map the main academic contributions on the subject. The results highlight the predominance of buyer-oriented structures, the growing importance of outsourcing and logistics services, as well as research gaps related to chain coordination, process integration, and the adoption of digital technologies. It was found that understanding the structure and complexity of the chain is essential to support strategic decisions by companies, governments, and support institutions, contributing to gains in competitiveness and resilience. As a contribution, this study reinforces the need for research that advances the incorporation of emerging themes, such as Industry 4.0, sustainability, traceability, and circularity, which are already shaping up as vectors of global transformation in the sector. It concludes that characterizing the textile and apparel supply chain broadens the understanding of its challenges and opportunities, providing support for its adaptation to the new demands of the international market.DOI: https://doi.org/10.56238/edimpacto2025.090-096